PENGARUH LATIHAN TARGET TERHADAP AKURASI SHOOTING FUTSAL - yarso, Dedi; Triansyah, Andika; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is the lack of accuary in futsal shooting in futsal extracurricular members of Haruniyah Islamic High School Pontianak so often when the player does not shoot exactly the desired target, not even closing the possibility of the ball soaring high. The purpose of this study is to determine the effect of target training on the accuracy of futsal shooting in futsal extracurricular members of Haruniyah Islamic High School Pontianak. The method used in this research is the experimental method. Subjects in research are students Extracurricular Islamic High School Pontianak totaling 20 students. Thisstudy uses a test instrument, while the test instrument used in the study is a shooting test, the test given is by dividing the field of goal that has been marked and given a number. Data analysis using t-test formula. The results of study obtained the value of ttest 4.159 > ttable 1.729 means that there is the effect of target training on the accuracy of futsal shooting on futsal extracurricular members at Islamic High School Pontianak. With an increase in the average pretest of 9.65 and 14.10 posttest so there is a 46.11% increase that occurs.Keywords: Variation of Practice, Shooting .